Affective Ratings of Pictures Related to Interpersonal Situations - Blekić, Wivine; Kandana Arachchige, Kendra; Wauthia, Erika; Simoes Loureiro, Isabelle; Lefebvre, Laurent; Rossignol, Mandy (Frontiers in Psychology, 2021)
Many studies require standardized and replicable protocols composed of emotional stimuli. To this aim, several databases of emotional pictures are available. However, there are only few images directly depicting interpersonal violence, which is a specific emotion evocative stimulus for research on aggressive behavior or post-traumatic stress disorder. The objective of the current study is to provide a new set of standardized stimuli containing images depicting interpersonal situations (both positive and negative). This will allow a sensitive assessment of a wide range of cognitions linked to social interaction (empathy, perspective taking, traumatic experiences, etc.). To this aim, 240 participants rated the valence and arousal of 79 pictures collected from online sources in 2018. Results showed (1) a distinctive pattern of valence and arousal regarding the picture content and (2) specific associations between those two dimensions. Taken together, these results suggest a good reliability of the selected images. In conclusion, our study provides an open access set of recent pictures depicting interpersonal situations along with normative valence and arousal ratings, that are available for download from: https://osf.io/ak4m7/?view_only=b1f31811d35e4b26a64eb6b65d01d467.